2010
DOI: 10.1093/neuonc/noq017
|View full text |Cite
|
Sign up to set email alerts
|

MGMT modulates glioblastoma angiogenesis and response to the tyrosine kinase inhibitor sunitinib

Abstract: Angiogenesis inhibitors, such as sunitinib, represent a promising strategy to improve glioblastoma (GBM) tumor response. In this study, we used the O(6)-methylguanine methyltransferase (MGMT)-negative GBM cell line U87MG stably transfected with MGMT (U87/MGMT) to assess whether MGMT expression affects the response to sunitinib. We showed that the addition of sunitinib to standard therapy (temozolomide [TMZ] and radiation therapy [RT]) significantly improved the response of MGMT-positive but not of MGMT-negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 41 publications
3
55
2
1
Order By: Relevance
“…It also has been suggested that MGMT has other (nonrepair) functions, as it has been reported to correlate with vascular endothelial growth factor receptors (VEGFRs) expression in vitro (43) and possibly play a role in integrating DNA damage/repair related signals with replication, cell cycle progression and genomic stability (44,45).…”
Section: Introductionmentioning
confidence: 99%
“…It also has been suggested that MGMT has other (nonrepair) functions, as it has been reported to correlate with vascular endothelial growth factor receptors (VEGFRs) expression in vitro (43) and possibly play a role in integrating DNA damage/repair related signals with replication, cell cycle progression and genomic stability (44,45).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of dimethylarginine dimethylaminohydrolase 2 was found to increase VEGF mrna expression and enhance tube formation (32). a recent study demonstrated that mGmt modulates GBM angiogenesis, and identified angiogenesis related-genes, including VEGF and its receptors in mGmtpositive GBm cells, demonstrating that VEGF receptors are differentially expressed according to mGmt status (15). Based on these findings, we hypothesized that reduced migration and tube formation in huVEcs may result from metronomic treatment of tmZ which leads to a decreased mGmt expression level, but also that metronomic treatment of tmZ may alter and reconstruct endogenous expression and secretion of VEGF and its receptors in huVEcs.…”
Section: Discussionmentioning
confidence: 98%
“…moreover, clinical research has reported that methylation of the mGmt promoter is useful to predict the responsiveness to alkylating agents (14). Recently, significant inhibition of glioma cell proliferation and survival was found to be dependent on the mGmt status (15). notably, one clinical study found that significant and prolonged depletion of O 6 -alkylguanine-dna-alkyltransferase (aGat) activity was produced by metronomic chemotherapy of tmZ (16).…”
mentioning
confidence: 99%
“…Western blotting was conducted as described previously (15). Membranes were probed for MGMT (clone MT5.1) CD29/integrin b 1 , FAK(pY397; all from BD Biosciences), FAK (Upstate), integrin a 5 (Cell Signaling), or b-actin (Sigma-Aldrich).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…We have previously characterized a novel inverse relationship between MGMT expression and GBM angiogenicity (15). Tumor angiogenesis and invasion, the major hallmarks of GBM aggressiveness share interdependent molecular mechanisms of regulation (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%